Interaction between fire and fragmentation in the successional stages of coastal dune grasslands of the southern Pampas, Argentina - Yezzi, Alejandra Lorena (2019)
Vegetation’s increased vulnerability to extrinsic disturbances is an important but less studied efect of natural habitat fragmentation. Fire is part of the evolutionary history of grassland ecosystems, but fragmentation by forest plantations can alter the fre regime and infuence their resilience. This study compares the successional trajectories after fre in continuous and fragmented grassland in terms of composition and abundance of plant species. Grassland fragments of varying sizes (0.1 to 2.5ha) surrounded by a forest matrix and grassland controls of an equivalent area in adjacent, non-fragmented sites were selected. Fire was associated with an increase in the abundance of exotic plants in the fragmented grassland whereas the continuous grasslands were much more resistant to invasion. These diferences in the species composition between fragments and continuous areas, which were limited to the smaller areas before the fre, were observed one year after the fre throughout the range of sizes analyzed. These results show the impact of fragmentation on grassland resilience and how the efects of this process become evident even months after a disturbance, highlighting the synergistic efect of habitat fragmentation and biological invasions, two factors identifed as the main forces of biodiversity erosion.